HOMOGENEUS MIXED PROBLEM FOR THE DAMPED CARRIER EQUATION - San Gil Jutuca, Luiz Pedro (1999)
This paper is concerned with the existence of global solutions of an initial and homogeneous boundary problem for the damped Carrier equation ... where M is a positive real function and p> 1.